2008
DOI: 10.3324/haematol.13012
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in situ hybridization improves the detection of 5q31 deletion in myelodysplastic syndromes without cytogenetic evidence of 5q-

Abstract: BackgroundMore than 50% of patients with myelodysplastic syndromes present cytogenetic aberrations at diagnosis. Partial or complete deletion of the long arm of chromosome 5 is the most frequent abnormality. The aim of this study was to apply fluorescence in situ hybridization of 5q31 in patients diagnosed with de novo myelodysplastic syndromes in whom conventional banding cytogenetics study had shown a normal karyotype, absence of metaphases or an abnormal karyotype without evidence of del(5q). Design and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 28 publications
3
27
2
Order By: Relevance
“…6 In the literature, several studies described discrepant results of karyotype and FISH analyses. 10,[14][15][16][17] In most instances, the cases with a discrepant result (positive by FISH only) had an insufficient number of metaphases or the chromosome morphology was poor. Pitchford et al recommended FISH in myelodysplastic syndrome patients only if an adequate karyotyping with at least 20 metaphases was not possible, since they were unable to demonstrate any advantage of FISH in the setting of an optimal banding analysis.…”
Section: Clinical Consequencesmentioning
confidence: 99%
“…6 In the literature, several studies described discrepant results of karyotype and FISH analyses. 10,[14][15][16][17] In most instances, the cases with a discrepant result (positive by FISH only) had an insufficient number of metaphases or the chromosome morphology was poor. Pitchford et al recommended FISH in myelodysplastic syndrome patients only if an adequate karyotyping with at least 20 metaphases was not possible, since they were unable to demonstrate any advantage of FISH in the setting of an optimal banding analysis.…”
Section: Clinical Consequencesmentioning
confidence: 99%
“…Several studies have demonstrated that the combination of FISH and CC analysis significantly improved the detection of abnormalities in the cytogenetic diagnosis of MDS [4][5][6][7][8][9][10][11]. Conversely, other studies have reported that FISH detected 6% or fewer additional abnormalities compared to CC analysis alone, and these studies suggested limiting FISH testing to cases with suboptimal karyotyping [12][13][14][15][16][17][18]. The examination of small sample sizes and the use of data collected from a single center might have contributed to these differing results.…”
Section: Introductionmentioning
confidence: 84%
“…However, the clinical role of FISH studies and the context in which FISH might provide additional information that is undetectable by CC analysis remain uncertain. Prior studies comparing CC and FISH panel testing in MDS have yielded conflicting results [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Several studies have demonstrated that the combination of FISH and CC analysis significantly improved the detection of abnormalities in the cytogenetic diagnosis of MDS [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Cytogenetic investigation should always include full karyotype analyses, since in many patients loss of cytogenetic response was indicated by only one metaphase with 5q deletion, whereas FISH analysis provided a negative result. Thus, FISH using a probe for the commonly deleted region in 5q [24] does not seem to be sufficient for follow-up analysis. Our results underline the importance of a close and careful cytogenetic follow-up even after reaching a CCyR, since the clone with 5q deletion may reappear, increase in size and acquire additional chromosome aberrations, indicating progression of the disease.…”
Section: Discussionmentioning
confidence: 99%